Genome-modified Caenorhabditis elegans expressing the human cytochrome P450 (CYP1A1 and CYP1A2) pathway: An experimental model for environmental carcinogenesis and pharmacological research - Chen, Yuzhi; Jiang, Yang; Sarvanantharajah, Nirujah; Apirakkan, Orapan; Yang, Mengqi; Milcova, Alena; Topinka, Jan; Abbate, Vincenzo; Arlt, Volker M; Stürzenbaum, Stephen R (Environment international, 2024)
Polycyclic aromatic hydrocarbons (PAHs), including the Group 1 human carcinogen benzo[a]pyrene (BaP), are produced by the incomplete combustion of organic matter and thus are present in tobacco smoke, charbroiled food and diesel exhaust. The nematode Caenorhabditis elegans is an established model organism, however it lacks the genetic components of the classical mammalian cytochrome P450 (CYP)-mediated BaP-diol-epoxide metabolism pathway. We therefore introduced human CYP1A1 or CYP1A2 together with human epoxide hydrolase (EPHX) into the worm genome by Mos1-mediated Single Copy Insertion (MosSCI) and evaluated their response to BaP exposure via toxicological endpoints. Compared to wild-type control, CYP-humanised worms were characterised by an increase in pharyngeal pumping rate and a decrease in volumetric surface area. Furthermore, BaP exposure reduced reproductive performance, as reflected in smaller brood size, which coincided with the downregulation of the nematode-specific major sperm protein as determined by transcriptomics (RNAseq). BaP-mediated reproductive toxicity was exacerbated in CYP-humanised worms at higher exposure levels. Collagen-related genes were downregulated in BaP-exposed animals, which correlate with the reduction in volumetric size. Whole genome DNA sequencing revealed a higher frequency of T > G (A > C) base substitution mutations in worms expressing human CYP1A1;EPHX which aligned with an increase in DNA adducts identified via an ELISA method (but not classical 32P-postlabelling). Overall, the CYP-humanised worms provided new insights into the value of genome-optimised invertebrate models by identifying the benefits and limitations within the context of the (3Rs) concept which aims to replace, reduce and refine the use of animals in research.
Keywords: cytochrom P-450 CYP1A2; Cytochrome P-450 CYP1A1; Humans; cytochrom P-450 CYP1A1; Benzo[a]pyrene; Carcinogenesis; geneticky modifikovaná zvířata; Cytochrome P-450 CYP1A2; lidé; zvířata; Caenorhabditis elegans; CYP1A2; Animals, Genetically Modified; karcinogeneze; Benzo(a)pyrene; CYP1A1; Animals; DNA adducts; RNAseq; benzopyren; Mutational patterns